Pendekatan Keadilan Restoratif Dalam Penanganan Tindak Pidana Pencurian Yang Dilakukan Oleh Anak - Nurfa Caesarini Putri (2019)
This research is titled Restorative Justice approach in handling criminal acts of theft committed by children. This research uses 3 (three) approaches, namely statute approach, case approach, and conceptual approach. There are 2 (two) problems that will be discussed in the next chapter of the handling of child matters through restorative justice approaches and Judgment on court in the prevention of criminal acts of theft by children. Most adult criminal are generally committed to crimes since becoming a child. For a child to commit crimes is not generally seen if not investigated yet or a very bad environment. This study discusses the imposition of imprisonment in children who commit criminal acts of theft. This research is considered important because researchers see still open children's opportunities to grow and develop reasonably, even if it has committed a crime without having to be convicted or impacted of prisonization. Since the restorative justice conceptually contains the idea and principle of establishing joint participation between children, Victims, and community groups to complete a criminal offence. Encouraging children to be responsible for victims or crimes that have caused injuries or losses to victims, As well as establishing responsibility for not repeating any criminal deeds ever undertaken. The concept of restorative justice also puts events or criminal acts not primarily as a form of violation of the law But rather as a violation by someone (a group of people) against a person (a group of people). The conclusion of this research is the restorative Justice approach to the Act still not in line based on facts, From a stage of investigation to the supervision